Pencegahan Stunting Pada Era New Normal di Puskesmas Sekaran - Mardiana Mardiana; Mursid Tri Susilo; Efa Nugroho; Latifah Rachamawati (Universitas Muhammadiyah Yogyakarta, 2022)
Based on the Nutrition Status Monitoring (PSG) data in 2019, the prevalence of stunting in Indonesia was recorded at 27.67 percent. This figure is still above the standard set by WHO, which should not exceed 20 percent. The prevalence of stunting in Central Java showed an increase from 2014 to 2017, while the prevalence of stunting in Semarang City was 21.0%. It is feared that the increased prevalence will continue to increase due to the low or even non-functioning posyandu in the new normal era. This condition causes the skill capacity of the cadres in anthropometric measurements to decrease. This was triggered by the concerns of most mothers about the transmission of Covid-19. This service aims to maintain and increase the activity capacity of posyandu cadres in the new normal era, especially in preventing stunting. The implementation method was carried out by counseling about stunting, training and assisting cadres in anthropometric measurements, filling out and interpreting the Towards Health Card (KMS), preparing stunting books and posyandu menus. Stages of activities include preparation, implementation, and evaluation of the program. The results of the service showed an increase in knowledge of cadres before and after being given education by 53%. In addition, there was a significant difference in the knowledge of the health care providers before and after the intervention.